The orphan framework as a new opportunity: an expert opinion. (November 2014) - Mariz, Segundo; Tsigkos, Stelios; Fregonese, Laura; Aarum, Stiina; Dehlink, Eleonora; Llinares, Jordi; Sepodes, Bruno
<x xml:space="preserve">Abstract</x> This is a review of the post-designation incentives framework that exists in Europe under its Orphan Medicinal Designation System. The aim of the article is to review and highlight specific regulatory mechanisms which are used or tailored to help in the development and licensing of products which receive an orphan designation. It is hoped that through this article there will be greater clarity of the post-designation incentives available to sponsors who obtain an Orphan Medicinal Designation.